2010
DOI: 10.1128/aac.01046-09
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxyphthalic Anhydride-Modified Chicken Ovalbumin Exhibits Potent and Broad Anti-HIV-1 Activity: a Potential Microbicide for Preventing Sexual Transmission of HIV-1

Abstract: Heterosexual transmission is the primary route by which women acquire human immunodeficiency virus (HIV)/AIDS. Thus, development of woman-controlled topical microbicides for prevention of sexual transmission of HIV is urgently needed. Here we report that 3-hydroxyphthalic anhydride-modified chicken ovalbumin (HP-OVA) exhibits potent antiviral activity against a broad spectrum of human immunodeficiency virus type 1 (HIV-1) isolates with different genotypes and biotypes. Its antiviral activity is correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 73 publications
1
69
0
Order By: Relevance
“…In previous studies, we demonstrated that the percentage of anhydride-modified residues was proportional to the entry-inhibitory activity of anhydride-modified proteins (23,25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, we demonstrated that the percentage of anhydride-modified residues was proportional to the entry-inhibitory activity of anhydride-modified proteins (23,25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2, the EC 50 of HP-HSA showed no significant change when it was mixed with serum from different species from that when it was mixed with Dulbecco modified Eagle medium (DMEM), while the EC 90 values increased slightly, but it still inhibited Zaire PsV entry by 90% at the micromolar scale. Our previous studies demonstrated that anhydride-modified proteins could be utilized as anti-HIV or anti-HPV microbicides (25,26,28). In order to determine whether HP-HSA could be developed as an anti-EBOV microbicide against the sexual transmission of EBOV, we tested the antiviral activity of HP-HSA against both Zaire PsV and Sudan PsV entry in human genital fluids, including seminal fluid (SF) and vaginal fluid simulant (VFS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the fourth day postinfection, 100 l of culture supernatants were collected from each well, mixed with equal volumes of 5% Triton X-100, and assayed for p24 antigen by ELISA. The inhibition of P20 and its variants on infection by the HIV-1 R5 strain Bal, the primary HIV-1 isolates, and the VSV-G pseudovirus was determined as described before (31). Briefly, 100 l of TZM-bl cells (1 ϫ 10 5 /ml) was precultured overnight and infected with a virus at 100 TCID 50 in the presence or absence of the test peptide overnight.…”
mentioning
confidence: 99%